2012
DOI: 10.1007/s10488-012-0424-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technologies Among People with Serious Mental Illness: Opportunities for Future Services

Abstract: Several national bodies have proposed using mobile technology to improve mental health services. But rates of current use and interest in using technology to enhance services among individuals with serious mental illness are uncertain. The authors surveyed 1,592 individuals with serious mental illness regarding their use of mobile devices and interest in using mobile technologies to enhance mental health services. Seventy-two percent of survey respondents reported currently owning a mobile device, a rate appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
216
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(223 citation statements)
references
References 9 publications
4
216
1
2
Order By: Relevance
“…Although DHTs hold significant promise for the improvement of various elements of behavioral health intervention, and surveys have indicated that people with SMI are enthusiastic about using technology [19,20], adoption has been slow, testing of outcomes from acceptability to effectiveness has been limited, and codified development and deployment strategies have been lacking [21][22][23][24][25][26][27][28]. These preliminary efforts need to be undertaken before their effectiveness can be tested and verified so that the resulting findings can be incorporated into the redesign and reconfiguration of DHTs to provide an optimal solution.…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%
“…Although DHTs hold significant promise for the improvement of various elements of behavioral health intervention, and surveys have indicated that people with SMI are enthusiastic about using technology [19,20], adoption has been slow, testing of outcomes from acceptability to effectiveness has been limited, and codified development and deployment strategies have been lacking [21][22][23][24][25][26][27][28]. These preliminary efforts need to be undertaken before their effectiveness can be tested and verified so that the resulting findings can be incorporated into the redesign and reconfiguration of DHTs to provide an optimal solution.…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%
“…MH app demand is high across censusdesignated areas, generations, and, to a degree, age, with less use by older adults [65]. Text messaging may be higher in urban areas [66] than rural areas [67].…”
Section: Innovations or Additions To Regular Traditional Treatmentsmentioning
confidence: 99%
“…MH app demand is high across censusdesignated areas, generations, and, to a degree, age, with less use by older adults [65]. Text messaging may be higher in urban areas [66] than rural areas [67].Psych apps are used mainly for many functions, including to: 1) communicate with other patients, caregivers, social supports, or providers; 2) augment psychotherapy and medical support with journaling, diaries, symptom tracking tools, and psychoeducation between clinic appointments; 3) (smart) monitor, that is, to use tools to predict relapse behavior or worsening affective symptoms, through sensors and data activity; 4) practice self-assessment and care through reflection about their symptoms; 5) make learning more interactive than traditional paper homework; and 6) organize, track, and thus monitor long-term their activities, moods, and therapy homework [22,68,69]. Since patients often forget key events between visits, logging "symptoms, affect, behavior, and cognitions close in time to experience" (known as ecological momentary assessment; EMA) helps with reporting of symptoms [70,71].…”
mentioning
confidence: 99%
“…In recent years, great efforts have been made to harness technology for improving mental health. One major strategy is to leverage the popularity and functionality of mobile phones [5]. The number of mobile phone users is expected to surpass 4.7 billion in 2017 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The number of mobile phone users is expected to surpass 4.7 billion in 2017 [6]. It is a ubiquitous, non-intrusive and 5 highly personal device, often equipped with sensors, which are capable to collect contextual and behavioral data both continuously and passively. Furthermore, mobile phone ownership in patients with affective disorders can be as high as 86% [5].…”
Section: Introductionmentioning
confidence: 99%